Gaseous and Particulate Matter Emissions from Road Transport: The Case of Kolkata, India - Dutta Abhishek; Jinsart Wanida (Environmental and Climate Technologies, 2021)
Indian cities are highly dependent on road transport for freight and passenger traffic movements. The estimated road transport led yearly emission inventory of pollutants for 25 million-plus population cities of India indicates vehicle stock as the critical contributor to air pollution in cities. During 2025 the city of Kolkata will be responsible for the emission of 21 668.24 Gg of CO2 followed by 272.81 Gg of CO, 98.21 Gg of NOX, 16.9 Gg of CH4, 93.39 Gg of SO2, 8.6 Gg of PM, and 38.55 Gg of HC due to its 2.79 million vehicles. The total vehicle stock of 25 leading Indian cities increased by 19 % during 2015–2017, and during the same period, Rajkot and Vadodara had the highest rise of 97 % and 94 % respectively. Out of 25 cities total CO2 (220 560 Gg) and CO (3185 Gg) vehicular emissions during 2017, Delhi was the highest contributor with 22 % and 20 % respectively followed by Bengaluru (12 %, 12 %), and Chennai (9 %, 8 %). The GHG emission per unit area of Kolkata during 2017, due to on-road vehicular emission, was the highest amongst the 25 cities of India. For Kolkata, cars were responsible for 35 % for CO2, 55 % of CO, 75 % of CH4, 27 % of PM, omnibuses for 41 % for NOX emission, taxis for 83 % of SO2, and two-wheelers for 36 % of HC emissions.